Effect of operating conditions on size of catechin/β-cyclodextrin nanoparticles prepared by nanoprecipitation and characterization of their physicochemical properties. (January 2022) - Han, Yanlong; Jia, Fuguo; Bai, Shigang; Xiao, Yawen; Meng, Xiangyi; Jiang, Longwei
Abstract: Nanoscale catechin/β-cyclodextrin inclusion complex (CA/β-CD IC) particles were prepared by nanoprecipitation method (absolute ethanol as precipitant). The effects of β-CD concentration, ethanol amount used for precipitating and ethanol dropping rate during precipitation on size of CA/β-CD IC particles were studied. Dynamic light scattering results indicated the above operating conditions have a significant effect on size of CA/β-CD IC nanoparticles. Nanoparticles can be further reduced to about 90 nm by adjusting operating parameters, such as reducing β-CD concentration, increasing amount of ethanol and decreasing ethanol drop rate. Inclusion ratio of CA/β-CD IC nanoparticles was about 71%. Fourier transform infrared spectroscopy results indicated that intermolecular hydrogen bond interactions maintain CA in cavity of β-CD. X-ray diffraction results showed the crystalline structure in nanoscale CA/β-CD IC was different from that in micro-size CA/β-CD IC. Differential scanning calorimetry and scanning electron microscopy results confirmed the formation of CA/β-CD IC nanoparticles. CA/β-CD IC nanoparticles displayed great storage stability and ionic strength stability, and exhibited excellent stability at pH 4–9. Release behavior of CA from CA/β-CD IC nanoparticles was controlled. The CA/β-CD IC nanoparticles have potential applications in nano-functional foods. Highlights: Catechin/β-cyclodextrin inclusion complex nanoparticles were successfully prepared. The size of nanoparticles can be controlled by adjusting the operating parameters. The inclusion complex nanoparticles presented new solid crystalline phase. The antioxidant stability of catechin was improved after encapsulation. Inclusion complex have potential applications in nano-functional foods.